2016
DOI: 10.1007/s40273-016-0402-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Diagnostic Definitions in Claims Data on Healthcare Cost Estimates: Evidence from a Large-Scale Panel Data Analysis of Diabetes Care in Japan

Abstract: Diabetes-related healthcare costs are sensitive to diagnostic definition methods. Determining appropriate diagnostic definitions can further advance healthcare cost research for diabetes and its applications in healthcare policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…It has been reported that medical costs for an individual with one diabetes‐related complication can be 1.2 times higher than that of an individual without any complications, and this increases by 1.8, 2, and 2.5 times when the number of complications increases to 2, 3, and 4, respectively 112 . It has also been reported that the average cost per‐patient‐per‐month associated with diabetes is estimated to be US$208 (95% CI, 207‐209) in Japanese patients using the JMDC data 113 . Retinopathy and renal failure add additional costs of US$97 and US$340, respectively.…”
Section: Recent Diabetes Studies In Japanmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that medical costs for an individual with one diabetes‐related complication can be 1.2 times higher than that of an individual without any complications, and this increases by 1.8, 2, and 2.5 times when the number of complications increases to 2, 3, and 4, respectively 112 . It has also been reported that the average cost per‐patient‐per‐month associated with diabetes is estimated to be US$208 (95% CI, 207‐209) in Japanese patients using the JMDC data 113 . Retinopathy and renal failure add additional costs of US$97 and US$340, respectively.…”
Section: Recent Diabetes Studies In Japanmentioning
confidence: 99%
“…112 It has also been reported that the average cost per-patientper-month associated with diabetes is estimated to be US$208 (95% CI, 207-209) in Japanese patients using the JMDC data. 113 Retinopathy and renal failure add additional costs of US$97 and US$340, respectively. These costs increase to US$2062 with retinopathy and US$3689 with renal failure when surgery or dialysis is performed.…”
Section: Diabetes-related Healthcare Costsmentioning
confidence: 99%
“…However, this analysis was subject to limitations associated with any inaccuracies or incompleteness of the ICD-10 codes and ATC codes used to identify diagnoses and medication use as well as lack of clinical information (e.g., to assess blood glucose control). Relatedly, while the methods used to identify patients with T2DM are consistent with prior studies using the same database, the effect of alternative criteria for identifying T2DM patients on the study findings is not known [ 3 ]. In addition, HIV/AIDS information was not available in JMDC, so the CCI may not be precise.…”
Section: Discussionmentioning
confidence: 96%
“…Type 2 diabetes mellitus (T2DM), the most common form of diabetes, affected about 7.6% of adults aged 20–79 years in Japan in 2015 [ 1 ] and accounted for approximately 4% of the national healthcare expenditure in 2014 [ 2 ]. The healthcare costs are particularly high among patients who develop diabetes-related complications, as demonstrated by a Japanese claims data study in 2016 [ 3 ]. As such, it is important to effectively manage patients with T2DM in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…We calculated a single utility value for those with T2DM with any complication based on multiple studies. Fukuda et al [12] thoroughly reported treatment costs for patients with T2DM and the proportion of T2DM-related complications using the Japan Medical Data Center Claims Database. We rst retrieved utility values for each T2DM-related complication from previous studies and then weighted each utility value based on the proportion reported to aggregate into one utility, which represents the average utility value for patients with T2DM with any complication (Table 1).…”
Section: Utilitymentioning
confidence: 99%